2021
DOI: 10.1001/jama.2021.10207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urate-Elevating Inosine on Early Parkinson Disease Progression

Abstract: IMPORTANCE Urate elevation, despite associations with crystallopathic, cardiovascular, and metabolic disorders, has been pursued as a potential disease-modifying strategy for Parkinson disease (PD) based on convergent biological, epidemiological, and clinical data.OBJECTIVE To determine whether sustained urate-elevating treatment with the urate precursor inosine slows early PD progression.DESIGN, PARTICIPANTS, AND SETTING Randomized, double-blind, placebo-controlled, phase 3 trial of oral inosine treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…A randomized, double-blinded, placebo-controlled safety, tolerability, and dose-ranging trial of oral inosine in PD (i.e., Safety of Urate Elevation in PD, SURE-PD) found that oral inosine titrated to mildly or moderately elevate the serum U levels is safe and well tolerated for up to 2 years (except for the development of kidney stones in 6% of those receiving inosine), leads to an increase in the cerebrospinal fluid concentration of U, and may show a trend towards a modest reduction in PD progression, especially in women [64]. Despite its good safety profile, a subsequent inosine trial, Effect of Urate-Elevating Inosine on Early Parkinson Disease Progression (SURE-PD3), showed no significant differences between the active and the placebo arms concerning the progression of PD [65].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blinded, placebo-controlled safety, tolerability, and dose-ranging trial of oral inosine in PD (i.e., Safety of Urate Elevation in PD, SURE-PD) found that oral inosine titrated to mildly or moderately elevate the serum U levels is safe and well tolerated for up to 2 years (except for the development of kidney stones in 6% of those receiving inosine), leads to an increase in the cerebrospinal fluid concentration of U, and may show a trend towards a modest reduction in PD progression, especially in women [64]. Despite its good safety profile, a subsequent inosine trial, Effect of Urate-Elevating Inosine on Early Parkinson Disease Progression (SURE-PD3), showed no significant differences between the active and the placebo arms concerning the progression of PD [65].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in a lack of PD intervention trials that target specific mechanistic changes in groups of individual patients defined according to the mechanism(s) that contribute to disease development/progression. The SURE-PD3 trial is an exception that targeted only individuals with low serum urate concentrations 9 . However, beyond the SURE-PD3 trial, there is typically no specific measurable biological signal for the success of a disease-modifying intervention for each disease within the PD umbrella 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some recent efforts indicate that the field may be moving forward from clinical diagnostic criteria-based enrollment. One example is the SURE-PD3 trial, where the study design purposely used an enrichment strategy (serum urate below the population median concentration), based on the expected mechanism of action of inosine, the study intervention ( Parkinson Study Group et al, 2021 ). Although, this particular study failed to meet its primary endpoint, we believe it to be an important example of how a biomarker-defined specific sub-population of PD, beyond just meeting clinical diagnostic criteria, can be feasibly employed in a large multicenter clinical trial.…”
Section: From Preclinical Success To Clinical Disappointment: Possibl...mentioning
confidence: 99%